2022
DOI: 10.1021/acsanm.2c04080
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Protein–Surfactant Nanoaggregates for Tunable Peptide Bond Hydrolysis by Polyoxometalate Nanoclusters

Abstract: The development of robust artificial proteases is of crucial importance for the study of proteins since natural proteases only retain their proteolytic activity under specific conditions. The presence of surfactants, which aid in solubilizing proteins and in probing their structure, is particularly detrimental to natural proteases. Therefore, artificial proteases that can function in the presence of surfactants are needed. Here, we report the hydrolysis of horse heart myoglobin (Mb) in the presence of a Zr(IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 65 publications
0
27
0
Order By: Relevance
“…82,88 Moreover, it was shown that the hydrolytic activity of [Zr(P 2 W 17 O 61 ) 2 ] 16-(Zr-WD 1:2) toward the dipeptide glycyl-L-histidine was preserved in the presence of anionic, neutral, or zwitterionic surfactants as the surfactants did not affect the binding of the dipeptide to the M-POM. 88 Furthermore, in the presence of surfactants, M-POMs have also been reported to be hydrolytically active toward several globular and water-soluble proteins, 85,86,89,90 as well as toward unstructured and insoluble proteins. 87,91 The hydrolytic activity of M-POMs toward proteins in the presence of surfactants has been determined to depend on: (i) the protein structure and pI, (ii) the structure of the surfactant (charge, size and polarity), (iii) the ease of exchange between the surfactant and the M-POM on the protein surface, as well as (iv) the influence of the surfactant on the speciation of the M-POM (Figure 5a).…”
Section: Reactivity Of M-poms Toward Peptides and Proteins In Surfact...mentioning
confidence: 99%
See 4 more Smart Citations
“…82,88 Moreover, it was shown that the hydrolytic activity of [Zr(P 2 W 17 O 61 ) 2 ] 16-(Zr-WD 1:2) toward the dipeptide glycyl-L-histidine was preserved in the presence of anionic, neutral, or zwitterionic surfactants as the surfactants did not affect the binding of the dipeptide to the M-POM. 88 Furthermore, in the presence of surfactants, M-POMs have also been reported to be hydrolytically active toward several globular and water-soluble proteins, 85,86,89,90 as well as toward unstructured and insoluble proteins. 87,91 The hydrolytic activity of M-POMs toward proteins in the presence of surfactants has been determined to depend on: (i) the protein structure and pI, (ii) the structure of the surfactant (charge, size and polarity), (iii) the ease of exchange between the surfactant and the M-POM on the protein surface, as well as (iv) the influence of the surfactant on the speciation of the M-POM (Figure 5a).…”
Section: Reactivity Of M-poms Toward Peptides and Proteins In Surfact...mentioning
confidence: 99%
“…Unlike natural proteases, which lose their activity in the presence of surfactants, it has been shown that M-POMs are still hydrolytically active in surfactant solutions. , This is highly important since surfactants can be used to probe the structure of proteins . Additionally, surfactants are typically used to dissolve poorly soluble proteins, such as membrane proteins, that are often underrepresented in proteomics studies despite their important roles in many biological processes .…”
Section: Hydrolytic Activity Of Pomsmentioning
confidence: 99%
See 3 more Smart Citations